2021
DOI: 10.1111/acel.13392
|View full text |Cite
|
Sign up to set email alerts
|

Dioscin elevates lncRNA MANTIS in therapeutic angiogenesis for heart diseases

Abstract: The major function of the circulatory system is to deliver oxygen and nutrients to the cells throughout body (Del Re et al., 2019;Kaelin et al., 2016). An insufficient blood supply, if not corrected in time, leads to depletion of oxygen and nutrients to vital organs, resulting in organ failure and death. As we know, coronary artery disease (CAD) and stroke caused by ischemia, a sudden and severe blockage of coronary or brain arteries, are one of the most common causes of death worldwide (Khera & Kathiresan, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…28 It was implied by Kong that Dioscin alleviated hypoxic-caused cardiac dysfunction in myocardial infarction via elevating the level of lncRNA MANTIS. 29 Dioscin improved myocardial infarction damage through adjusting BMP4/NOX1-mediated inflammation. 30 In addition, Dox was reported as an effective and commonly used to treat hematological and solid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…28 It was implied by Kong that Dioscin alleviated hypoxic-caused cardiac dysfunction in myocardial infarction via elevating the level of lncRNA MANTIS. 29 Dioscin improved myocardial infarction damage through adjusting BMP4/NOX1-mediated inflammation. 30 In addition, Dox was reported as an effective and commonly used to treat hematological and solid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA Crnde also suppresses CFs activation and alleviates DCM-associated cardiac fibrosis through negative feedback regulation of Smad3 transcriptional activation [ 145 ]. Dioscin, a glucoside saponin isolated from Dioscorea nipponica Makino , reduced MI-induced cardiac fibrosis by upregulating lncRNA MANTIS to promote the expression of angiogenesis-related genes such as SOX18, SMAD6, and COUP-TFII [ 146 ]. Meanwhile, histone demethylase JARID1B could also regulate lncRNA MANTIS and restrict the expression of angiogenesis-related genes such as SMAD6 [ 153 ].…”
Section: Rna In Cfs Activation and Cardiac Fibrosismentioning
confidence: 99%
“…The protective effects are associated with mitochondrial function, including alleviating mitochondrial oxidative stress, de-activation of respiratory chain enzymes, postponing mitochondrial Kreb's cycle, and maintenance of mitochondrial membrane potential ( ψ) and ATP content (8)(9)(10). Dioscin, a natural steroid saponin isolated from the root bark of wild dioscorea nipponica, is reported to treat MI by promoting angiogenesis (11). Additionally, it was reported that dioscin maintains mitochondrial dynamics, which rescues silicosis by reducing mitochondrial-dependent apoptosis (12).…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, our results showed that dioscin could alleviate MI via attenuate mitochondrial malfunction. Infarction mouse model was generated through ligature of the left anterior descending (LAD) as described previously with male mice (11). Briefly, mice were anesthetized with 1.5-2% isoflurane, and then a left thoracotomy and pericardiotomy was performed.…”
Section: Introductionmentioning
confidence: 99%